Understanding Barriers to Linking High Risk Heterosexual African American Women to Care in the Upper South - Jill E. Rowe (HIV/AIDS Research and Treatment-Open Journal, 2016)
As part of Centers for Disease Control and Prevention’s (CDC’s) HIV prevention strategic plan through 2010,1 4 national goals were identified to reduce by half the new HIV infections in the United States. One of the 4 goals is to strengthen the national capacity to monitor the human immunodeficiency virus (HIV) epidemic to better direct and evaluate prevention efforts. In response to these goals, the CDC awarded funds to state health departments to develop and implement a surveillance system to monitor behaviors that put people at risk for HIV infection in metropolitan statistical areas (MSA) with high incidence of human immunodeficiency virus infection and acquired immune deficiency syndrome (HIV/AIDS).